The Analysis of Jargon Formation in Online Trading: A Case Study of Jargon Formation in Forum Jual Beli Kaskus - Linda Nurmala (Passage, 2013)
This study was aimed to reveal jargon formation in FJB Kaskus postings and investigate context of situation underlying the use of jargons. The data used in this research is in the form of online threads or postings from Kaskus FJB Forum. To analyze the formation of the jargons, the theories used were from Bauer (1983), Yule (1996), O'Grady Guzman (1996), and Stageberg (2000), while Hyme’s (1974) theory is used to analyze the context of situation. The result shows that there are 51 jargons with the total of 365 occurrences that can be divided into 10 types of jargon formation: abbreviation, clipping, clipped compounds, borrowing, coinage, derivation (prefix, sufix, prefix+afix), reduplication, and antonomasia. Those jargons were used in various situations depending on the context. Most of them are used in greetings, offerings, and in giving notice with various tone in formal and informal registers. Keywords: Jargon, Jargon Formation, Context Of Situation, Online Trading, Kaskus